Reactivation of Late Paleozoic structures during the Cenozoic deformation in the Cordón del Plata range and Southern Precordillera (Mendoza, Argentina) - Giambiagi, Laura Beatriz (2014)
The tectonic style of the eastern morphostructural units of the Central Andes between 32°20´ and 33°20´S is strongly influenced by pre-Andean structures, especially those developed during the Early Permian San Rafael compressional orogeny. In this paper we argue that first order features of the eastern ranges of the Andes, the Cordón del Plata range and the Southern Precordillera, have been shaped in large part by this event. Our data suggest that the double verging character of the Andean Precordillera fold-and-thrust belt is mainly the result of the reactivation of Late Paleozoic structures that conform a fold and thrust belt, with distinct characteristics north and south of 33°S. The northern sector of the belt corresponds to a bivergent system, while the southern sector had a notable east vergence. The sharp disappearance of the Precordillera morphostructural unit south of 33°S is inferred here to be related to the distribution of Permian structures.